Recent cocaine use and memory impairment in HIV. Issue 6 (2nd November 2021) - Litvin, Pavel Y.; Siders, Craig A.; Waite, Erin N.; Woo, Ellen; Romero, Elizabeth; Foley, Jessica; Ettenhofer, Mark L.; Gooding, Amanda L.; Castellon, Steven; Hinkin, Charles; Wright, Matthew J.
Abstract: Both Human Immunodeficiency Virus (HIV) and cocaine use have been associated with impairment in neuropsychological functioning. The high comorbidity between HIV and cocaine use highlights the importance of ascertaining whether there is a compounding effect of cocaine use in individuals with HIV. Among neuropsychological domains impacted by HIV, verbal memory deficits have received substantial attention partly because they have been associated with declines in functional status in HIV positive individuals. We collected California Verbal Learning Test-II data from HIV participants who met lifetime diagnostic criteria of cocaine abuse and/or dependence (HIV/CocDx+, N = 80 & HIV/CocDx−, N = 30, respectively) and those with and without recent cocaine use, which was confirmed by toxicology analysis (HIV/Coc+, N = 56 & HIV/Coc−, N = 57, respectively). The Item Specific Deficit Approach (ISDA) was employed to determine any additional cocaine-associated deficits in encoding, consolidation, and retrieval, which attempts to control for potential confounding factors of memory such as attention. Using conventional methods of evaluating memory profiles, we found that the HIV/Coc + group demonstrated worse learning, immediate and delayed free recall, and recognition in contrast to the HIV/Coc − group; although using the ISDA, we found that encoding was the only significant difference between HIV/Coc + and HIV/Coc-participant, with HIV/Coc − performing better. Our data suggest that for individuals with HIV, cocaine use is associated with a temporary decline in verbal memory, is characterized by greater encoding deficits, and these effects may reduce with abstinence. Clinically, our findings suggest that reduced encoding is the likely contributor to verbal memory decline in HIV/Coc + and these effects are partially reversible—at least to the level of their HIV/Coc − counterparts.